2018
DOI: 10.1101/426635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The folded X-pattern is not necessarily a statistical signature of decision confidence

Abstract: Recent studies have traced the neural correlates of confidence in perceptual choices using statistical signatures of confidence. The most widely used statistical signature is the folded X-pattern, which was derived from a standard model of confidence assuming an objective definition of confidence as the posterior probability of making the correct choice given the evidence. The folded X-pattern entails that confidence as the subjective probability of being correct equals the probability 0.75 if the stimulus in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Previous modelling work has unraveled boundary conditions of this first diagnostic signature, the interaction between evidence strength and choice accuracy. Model simulations have shown that this interaction disappears if stimuli are only probabilistically related to choices 25 , and if the statistical model has knowledge about evidence strength on the single-trial level 26 . Remarkably, however, no previous work has unraveled the role of time in this signature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous modelling work has unraveled boundary conditions of this first diagnostic signature, the interaction between evidence strength and choice accuracy. Model simulations have shown that this interaction disappears if stimuli are only probabilistically related to choices 25 , and if the statistical model has knowledge about evidence strength on the single-trial level 26 . Remarkably, however, no previous work has unraveled the role of time in this signature.…”
Section: Discussionmentioning
confidence: 99%